Language style (mis)matching: Consuming entertainment media from someone unlike you is linked to positive attitudes - David M. Markowitz (Scientific Reports)
Abstract Prior work suggests people often match with conversational partners by using a common rate of style words (e.g., articles, pronouns). Indeed, such language style matching (LSM) has associated positively with downstream social and psychological dynamics like cooperation, liking, and well-being. To what degree is LSM predictive of positive attitudes in entertainment media settings? The current two-study paper addressed this question by collecting participants’ writing style with three diverse prompts, and then having them consume a random selection of TED talks (Study 1) and videotaped podcast narratives (Study 2). The evidence suggested less LSM was associated with positive attitudes (e.g., an interest in watching another video by the speaker, feeling connected to the speaker). Mediation analyses revealed the negative relationship between LSM and positive attitudes was explained by one’s novelty need satisfaction. Implications for LSM research, plus character construction and narrative development in media psychology, are discussed.